Optical density of bone repair after implantation of homogenous demineralized dentin matrix in diabetic rabbits - Gomes, Mônica Fernandes [UNESP]; Destro, Maria Fernanda de Souza Setúbal; Banzi, Éfani Caroline de Freitas [UNESP]; Vieira, Evanice Menezes Marçal; Morosolli, Aline Rose Cantarelli; Goulart, Maria das Graças Vilela [UNESP] (FapUNIFESP (SciELO), 2008)
This research evaluated the bone repair process after implantation of homogenous demineralized dentin matrix (HDDM) in surgical defects in the parietal bone of rabbits with alloxan-induced diabetes, using a polytetrafluorethylene (PTFe) barrier for guided bone regeneration. Thirty-six rabbits were used and divided into four groups: control (C, n = 12), diabetic (D, n = 12, left parietal bone), diabetic with PTFe (DPTFe, same 12 rabbits, right parietal bone), and diabetic with PTFe associated to HDDM (D-PTFe+HDDM, n = 12). Bone defects were created in the parietal bone of the rabbits and the experimental treatments were performed, where applicable. The rabbits were sacrificed after 15, 30, 60 and 90 days. The bone defects were examined radiographically and by optical density (ANOVA and Tukey test, p < .05). The radiographic findings showed that the D-PTFe+HDDM group presented greater radiopacity and better trabecular bone arrangement when compared to that of the C, D and D-PTFe groups. The statistical analysis showed significant differences in the optical density of the newly formed bone among the studied groups. It was possible to conclude that HDDM was biocompatible in diabetic rabbits.
Keywords: Bone density; Bone regeneration; Dentin; Diabetes mellitus; Guided tissue regeneration; alloxan; biomaterial; Demineralized Dentin Matrix; politef; animal; bone density; bone development; bone regeneration; dentin; disease model; drug effect; experimental diabetes mellitus; metabolism; methodology; physiology; prostheses and orthoses; rabbit; skull; tissue regeneration; Alloxan; Animals; Biocompatible Materials; Bone Density; Bone Regeneration; Diabetes Mellitus, Experimental; Disease Models, Animal; Guided Tissue Regeneration; Osteogenesis; Parietal Bone; Polytetrafluoroethylene; Prostheses and Implants; Rabbits